Implementasi Kebijakan Pemungutan Pajak Bumi dan Bangunan Pedesaan dan Perkotaan (Pbb-P2) di Kabupaten Gianyar - Ida Bagus Made Mulyarsa (Journal of Contemporary Public Administration, 2022)
The Government Gianyar Regency is one of the districts that collects rural and urban land and building taxes (PBB-P2) in accordance with Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. One of the efforts made is by collaborating with financial institutions such as Bank BPD Bali, BRI, LPD and cooperatives that collaborate in collection. The research objective was to determine the implementation of PBB-P2 tax collection policy and the factors causing the PBB-P2 collection not maximally. Using the theory of Van Meter and Van Horn. This research was conducted at the Regional Financial and Asset Management Agency of Gianyar Regency (BPKAD) using qualitative research methods. The results of the research on the implementation of PBB-P2 collection policy at BPKAD Gianyar Regency show that it is not optimal. Where the results of the discussion show that the size and objectives of the policy have been guided by Law 28 of 2009 on local taxes and levies. Resources are generally adequate. The characteristics of the executing agent are running quite well where the organizational structure can be used as a variable that explains the character of the organization. Communication between organizations and implementing activities has not run optimally so that various obstacles in service are still found.